The Soil–Plant Continuity of Rare Earth Elements: Insights into an Enigmatic Class of Xenobiotics and Their Interactions with Plant Structures and Processes - Angela Martina; Lorenzo Ferroni; Elena Marrocchino (Journal of Xenobiotics)
Rare earth elements (REEs) are increasingly present in the environment owing to their extensive use in modern industries, yet their interactions with plants remain poorly understood. This review explores the soil–plant continuum of REEs, focusing on their geochemical behavior in soil, the mechanisms of plant uptake, and fractionation processes. While REEs are not essential for plant metabolism, they interact with plant structures and interfere with the normal functioning of biological macromolecules. Accordingly, the influence of REEs on the fundamental physiological functions of plants is reviewed, including calcium-mediated signalling and plant morphogenesis. Special attention is paid to the interaction of REEs with photosynthetic machinery and, particularly, the thylakoid membrane. By examining both the beneficial effects at low concentrations and toxicity at higher levels, this review provides some mechanistic insights into the hormetic action of REEs. It is recommended that future research should address knowledge gaps related to the bioavailability of REEs to plants, as well as the short- and long-range transport mechanisms responsible for REE fractionation. A better understanding of REE–plant interactions will be critical in regard to assessing their ecological impact and the potential risks in terms of agricultural and natural ecosystems, to ensure that the benefits of using REEs are not at the expense of environmental integrity or human health.